Tests for lowvertical emittance at diamond using let algorithm - Liuzzo, S; Biagini, M; Raimondi, P; Bartolini, R (2011)
We present the results of a campaign of measurements recently performed at the Diamond Light Source, aimed at achieving a low vertical emittance using the Low Emittance Tuning (LET) Algorithm developed for the SuperB factory. The tests have been focused on the comparison of the method to the LOCO algorithm, that is currently used at Diamond. Beam position monitor tilts estimation and multiple coupling response matrices have been introduced in the algorithm in order to optimize the procedure. After a few fast iterations (5-6 min per iteration) using vertical correctors and skew quadrupoles, very low vertical dispersion and emittance coupling, comparable to those obtained by LOCO, have been measured. Copyright © 2011 by IPAC'11/EPS-AG.